The Effects of Advertising and Promotion on Consumers’ Buying Decision at the Car Boot Flea Market, in Durban - Michael Mbhekeni SHAZI; Nishika CHETTY (Expert Journal of Marketing, 2021)
Trading in the informal sector has seen a rapid growth in the developing as well as the developed economies in the last few decades. Consequently, the concept ‘flea market’ has gained renewed attention. The study aimed at identifying the preferred advertising and promotional strategies used by traders and how these strategies influence buying decisions in a flea market context. The study adopted a quantitative method using a non-probability convenience sample of 105 consumers attending the Car Boot Flea Market in the City of Durban, South Africa. Results indicated that as there is a need to save money, pricing of items was found to have a strong influence on the buying decision but consumers also look for a good offer, a clean attractive display of the products, an opportunity to test the product before buying and finding a product that the consumer has been seeking for a long time. Traditional marketing activities like calling out prices, issuing pamphlets and using other tactics to attract consumers have little effect on the consumers’ decision to buy at the market. Traders must develop a good reputation and the skills to demonstrate to consumers that an attractive offer is being made while still making a profit and be prepared to tailor their promotional messages to specific segments and thus make it easy for consumers to find goods of interest.